Bilateral Reference for High-Resolution Dichotomous Image Segmentation - Peng Zheng; Dehong Gao; Deng-Ping Fan; Li Liu; Jorma Laaksonen; Wanli Ouyang; Nicu Sebe (CAAI Artificial Intelligence Research)
We introduce a novel bilateral reference framework (BiRefNet) for high-resolution dichotomous image segmentation (DIS). It comprises two essential components: the localization module (LM) and the reconstruction module (RM) with our proposed bilateral reference (BiRef). LM aids in object localization using global semantic information. Within the RM, we utilize BiRef for the reconstruction process, where hierarchical patches of images provide the source reference, and gradient maps serve as the target reference. These components collaborate to generate the final predicted maps. We also introduce auxiliary gradient supervision to enhance the focus on regions with finer details. In addition, we outline practical training strategies tailored for DIS to improve map quality and the training process. To validate the general applicability of our approach, we conduct extensive experiments on four tasks to evince that BiRefNet exhibits remarkable performance, outperforming task-specific cutting-edge methods across all benchmarks. Our codes are publicly available at https://github.com/ZhengPeng7/BiRefNet.